Sustainable production of biosurfactant by Issatchenkia orientalis UCP 1603 using renewable substrates (Research, Society and Development, 2022)
Biological surfactants are amphipathic molecules produced by microorganisms and are considered multifunctional compounds of the 21st century. The current work aimed to use low-cost renewable substrates for economic production of biosurfactant by Issatchenkia orientalis UCP 1603. Fermentations were carried out at 28°C and 150 rpm for 72 h, using agro-industrial by-products (cassava wastewater, corn steep liquor and post-frying soybean oil) as substrates, according to a 23 full-factorial design (FFD) to identify their influence on biosurfactant production. The results showed the ability of the yeast to produce biosurfactant in all conditions of FFD, standing out the condition 4 due to the greatest reduction of surface tension (from 72 to 29.7 mN/m). The statistical analyses evidenced the significative influence of cassava wastewater and corn steep liquor on biosurfactant production. The tensoactive properties of the biomolecule were confirmed by parafilm test and emulsification index. This study evidenced I. orientalis as promising biosurfactant-producing yeast, with excellent ability and higher biotechnological potential for transformation of agro-industrial by-products.